Dukungan Suami Dengan Perilaku Agresif Ibu Rumah Tangga - Buidman, M. Elyas Arif; Umami, Novita; Yuhbaba, Zidni Nuris; Astutik, Emi Eliya; Erdah Suswati, Wahyi Sholehah (Indonesian Health Science Journal, 2025)
Background: Husband's support is a form of manifestation of attention and affection. Low affection and support from husbands to wives will result in aggressive behavior. Forms of aggressive behavior carried out by mothers include hitting their children, saying harsh words such as cursing. Objective: This study aims to determine the relationship between husband's support and housewives' aggressive behavior. Method: This research method uses quantitative methods using a cross sectional design. The sample in this study consisted of 100 housewives using a proportional sampling technique. The independent variable is husband's support, the dependent variable is aggressive behavior. This research instrument uses a husband's support questionnaire with 10 statements and an aggressive behavior questionnaire with 21 statements which are valid and reliable. Statistical tests use the gamma test. Results: The research results show that husband's support is in the high category as much as 64%, aggressive behavior is in the low category 78% of this research shows that there is a relationship between husband's support and aggressive behavior of housewives with a correlation coefficient value of -0.702 and a P value = 0.001 ≤ 0.05. Conclusion: Husband's support is a very important factor for the family. If a mother lacks support from her husband, this will result in aggressive behavior.